2010
DOI: 10.1029/2009jc005853
|View full text |Cite
|
Sign up to set email alerts
|

Wave‐turbulence interaction and its induced mixing in the upper ocean

Abstract: [1] In the ocean, interaction among the mean current, the surface waves, and turbulence is a major mechanism for energy transfer from surface waves to the turbulence field. This process is associated with attenuation of surface waves. This paper deals with waveturbulence interaction and its induced mixing using field observations and a onedimensional, level 2.5 turbulence closure model. The results show that both the turbulence kinetic energy dissipation rate and the vertical mixing induced by wave-turbulence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
110
1
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(124 citation statements)
references
References 60 publications
10
110
1
3
Order By: Relevance
“…If the wave spectrum is narrow enough bulk parameters can indeed characterize the effect of the irregular wave motion with sufficient accuracy, as opposed to deriving turbulent mixing and shear production from the spectrum [19]. In the absence of a wave spectrum (modeled or measured), many researchers successfully applied mixing parametrizations based on bulk characteristic [14,23] but it has to be underlined that several studies reported that model results improve significantly by using a 2D spectral wave model since wave mixing can be overestimated by bulk parametrizations [25,26].…”
Section: Model Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…If the wave spectrum is narrow enough bulk parameters can indeed characterize the effect of the irregular wave motion with sufficient accuracy, as opposed to deriving turbulent mixing and shear production from the spectrum [19]. In the absence of a wave spectrum (modeled or measured), many researchers successfully applied mixing parametrizations based on bulk characteristic [14,23] but it has to be underlined that several studies reported that model results improve significantly by using a 2D spectral wave model since wave mixing can be overestimated by bulk parametrizations [25,26].…”
Section: Model Descriptionmentioning
confidence: 99%
“…(8) to observations [26]. Huang and Qiao [23] determined its value as 1 for a medium-size lake which is featured by wave motion similar to that of Lake Balaton. The observed wave height and period were 0.25 m and 4 s [27].…”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…These types of models typically predict low levels of mixing near the surface due to the assumption of wall-type flow near the surface, which is inconsistent with the observation that particles are efficiently mixed downward during storms (e.g., oil droplets and pelagic eggs). Also, observations of turbulent dissipation in the upper ocean show deviations from law-of-the-wall behavior near the surface (Huang and Qiao 2010;Sutherland et al 2013). Consequently, diffusivity profiles from second-order closures often yield unrealistic results for plankton diffusion (Curtis et al 2007).…”
mentioning
confidence: 99%